Differential effects of variation in athletes training on myocardial morphophysiological adaptation in men: Focus on I-123-MIBG assessed myocardial sympathetic activity - Miranda, Douglas Pinheiro [UNESP]; Santos, Marcelo Jose dos; Cury Salemi, Vera Maria; Caparelli de Oliveira, Edmundo Pereira; Verberne, Hein J.; Rocha, Euclides Timoteo da (Springer, 2014)
High intensity systematic physical training leads to myocardial morphophysiological adaptations. The goal of this study was to investigate if differences in training were correlated with differences in cardiac sympathetic activity.58 males (19-47 years), were divided into three groups: strength group (SG), (20 bodybuilders), endurance group (EG), (20 endurance athletes), and a control group (CG) comprising 18 healthy non-athletes. Cardiac sympathetic innervation was assessed by planar myocardial I-123-metaiodobenzylguanidine scintigraphy using the early and late heart to mediastinal (H/M) ratio, and washout rate (WR).Left ventricular mass index was significantly higher both in SG (P < .001) and EG (P = .001) compared to CG without a statistical significant difference between SG and EG (P = .417). The relative wall thickness was significantly higher in SG compared to CG (P < .001). Both left ventricular ejection fraction and the peak filling rate showed no significant difference between the groups. Resting heart rate was significantly lower in EG compared to CG (P = .006) and SG (P = .002). The late H/M ratio in CG was significantly higher compared to the late H/M for SG (P = .003) and EG (P = .004). However, WR showed no difference between the groups. There was no significant correlation between the parameters of myocardial sympathetic innervation and parameters of left ventricular function.Strength training resulted in a significant increase in cardiac dimensions. Both strength and endurance training seem to cause a reduction in myocardial sympathetic drive. However, myocardial morphological and functional adaptations to training were not correlated with myocardial sympathetic activity.
Keywords: Athletes; evaluation; heart; sympathetic activity; endurance; strength